Factors associated with suicidal ideation among puerperal women in the context of public health: integrative review - Santos, Giovanna Vitória Aragão de Almeida; Silva Junior, Fernando José Guedes da; Costa, Ana Paula Cardoso; Sales, Jaqueline Carvalho e Silva (Revista de Enfermagem da UFPI, 2024)
Objective: To synthesize scientific evidence about the factors associated with suicidal ideation in the puerperal period in the context of public health. Methods: Integrative review conducted by the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol, carried out in July 2022, in the Medical Literature Analysis and Retrieval System Online, Web of Science, Latin American and Caribbean Literature in Health Sciences, Nursing Database, Spanish Bibliographic Index of Health Sciences, PsycINFO and Cumulative Index to Nursing and Allied Health Literature. Results: Seven studies were selected to compose this review. Factors associated with suicidal ideation in the puerperal period were younger, single, unemployed women, having an unemployed partner, having experienced intimate partner violence, having faced stressful events during pregnancy, previous experiences of abortion and marital dissatisfaction, depressive symptoms and other mental disorders (mood disorders, hypomanic symptoms, neuroticism and psychoticism). High self-esteem aimed to reduce ideas of suicide during the postpartum period. Being primigravid, having a harmonious relationship with the mother-in-law, and marital satisfaction were presented as protective factors. Conclusion: The synthesis of the studies showed the association of psychosocial, physiological and sociodemographic factors with suicidal ideation among puerperal women, as well as protective factors.